Building a Student-Centered Organizational Culture: Case Study of the Ateneo de Manila University - Cuyegkeng, Ma. Assunta C (Archīum Ateneo, 2021)
The movement away from teacher-centered toward student-centered learning and teaching (SCLT) in higher education has intensified in recent decades. Yet in spite of its widespread use in literature and policy documents, SCLT remains somewhat poorly defined, under-researched and often misinterpreted. Against this backdrop, The Routledge International Handbook of Student-Centered Learning and Teaching in Higher Education offers an original, comprehensive and up-to-date overview of the fundamentals of SCLT and its discussion and applications in policy and practice. Bringing together 71 scholars from around the world, the volume provides examples of good practice that display how instructional expertise manifests itself, and critically discusses challenges, new directions and developments in pedagogy, course and study program design, and classroom practice and assessment. Including reviews of theoretical, conceptual, methodological issues and case study examples, each chapter also considers implications for implementing SCLT across various contexts in higher education. An essential resource, this book uniquely offers researchers, educators and students in higher education new insights into the roots, latest thinking, practices and evidence surrounding SCLT in higher education.